Biomarker selection depends on gene function and organ: the case of the cytochrome P450 family genes in freshwater fish exposed to chronic pollution - Jorge Cortés-Miranda; Noemí Rojas-Hernández; Gigliola Muñoz; Sylvia Copaja; Claudio Quezada-Romegialli; David Veliz; Caren Vega-Retter (PeerJ, 2024)
Pollution and its effects have been of major concern in recent decades. Many strategies and markers have been developed to assess their effects on biota. Cytochrome P450 (CYP) genes have received significant attention in this context because of their relationship with detoxification and activation of exogenous compounds. While their expression has been identified as a pollution exposure biomarker, in most cases, it has been tested only after acute exposures and for CYP genes associated with exogenous compounds. To elucidate CYP gene expression patterns under chronic pollution exposure, we have used the silverside Basilichthys microlepidotus as a model, which inhabits the Maipo River Basin, a freshwater system with different pollution levels. We performed next-generation RNA sequencing of liver and gill tissues from polluted and non-polluted populations. We found most CYP genes were not dysregulated by pollution, and the seven genes that were present and differentially expressed in liver and gill were mainly downregulated. Three CYP genes associated with exogenous compounds showed differential expression in the gill, while four CYP genes associated with endogenous compounds showed differential expression in the liver. The findings presented here highlight the importance of CYP genes, his family, tissues and his interaction in the context of pollution biomarkers use.